Epigenetic histone acetylation modulating prenatal Poly I:C induced neuroinflammation in the prefrontal cortex of rats: a study in a maternal immune activation model - Su, Yueqing; Lian, Jiamei; Chen, Shiyan; Zhang, Wenchang; Deng, Chao (Frontiers in Cellular Neuroscience, 2022)
Introduction: Neuroinflammation in the central nervous system, particularly the prefrontal cortex (PFC), plays a role in the pathogenesis of schizophrenia, which has been found to be associated with maternal immune activation (MIA). Recent evidence suggests that epigenetic regulation involves in the MIA-induced neurodevelopmental disturbance. However, it is not well-understood how epigenetic modulation is involved in the neuroinflammation and pathogenesis of schizophrenia. Methods: This study explored the modulation of histone acetylation in both neuroinflammation and neurotransmission using an MIA rat model induced by prenatal polyriboinosinic-polyribocytidylic acid (Poly I:C) exposure, specifically examining those genes that were previously observed to be impacted by the exposure, including a subunit of nuclear factor kappa-B (Rela), Nod-Like-Receptor family Pyrin domain containing 3 (Nlrp3), NMDA receptor subunit 2A (Grin2a), 5-HT2A (Htr2a), and GABAA subunit β3 (Gabrb3). Results: Our results revealed global changes of histone acetylation on H3 (H3ace) and H4 (H4ace) in the PFC of offspring rats with prenatal Poly I:C exposure. In addition, it revealed enhancement of both H3ace and H4ace binding on the promoter region of Rela, as well as positive correlations between Rela and genes encoding histone acetyltransferases (HATs) including CREB-binding protein (CBP) and E1A-associated protein p300 (EP300). Although there was no change in H3ace or H4ace enrichment on the promoter region of Nlrp3, a significant enhancement of histone deacetylase 6 (HDAC6) binding on the promoter region of Nlrp3 and a positive correlation between Nlrp3 and Hdac6 were also observed. However, prenatal Poly I:C treatment did not lead to any specific changes of H3ace and H4ace on the promoter region of the target genes encoding neurotransmitter receptors in this study. Discussion: These findings demonstrated that epigenetic modulation contributes to NF-κB/NLRP3 mediated neuroinflammation induced by prenatal Poly I:C exposure via enhancement of histone acetylation of H3ace and H4ace on Rela and HDAC6-mediated NLRP3 transcriptional activation. This may further lead to deficits in neurotransmissions and schizophrenia-like behaviors observed in offspring.